Defiant bride. - Bothwell, Jean (Harcourt, Brace & World, 1969)
In seventeenth-century India the romantic destiny of a seventeen-year-old Nomad girl is markedly changed when the powerful ruler Akbar decides to annex the hill country where her people wander.